Detection of Carbapenemase Producing Uropathogens in a Tertiary Care Hospital, Chattogram - Akhtar, Sharmin; Haque, Md Ehsanul; Kalam, Abul; Akther, Shamima; Alam, Sultana Ruma (IAHS Medical Journal, 2024)
Background: Antimicrobial Resistance (AMR) posses a complex threat to global health security and universal health coverage. Gram negative bacteria have developed the broadest spectrum of resistance due to multiple structural adaptions and antibiotic degradation enzymes including Extended Spectrum Beta Lactamase, AmpC Cephalosporinase and Carbapenemase. Carbapenemases are beta-lactamases with versatile hydrolytic capacities. They have the ability to hydrolyze penicillins, cephalosporins, monobactam, and carbapenems. The classical phenotypic method cannot provide an efficient means of diagnosis of the carbapenemase producer. Multiplex PCR also helps in simultaneous detection of various genes, reducing materials, manpower and helps in determining epidemiology related to these genes and infection subsidence. This study was designed to determine the presence of carbapenemase producers among the carbapenem resistant uropathogens and to compare the phenotypic method with genotypic method along with the antimicrobial resistance patterns. Materials and methods: This cross-sectional study was carried out in the Department of Microbiology Chittagong Medical College, Chattogram for quantitative culture, mCIM test, and multiplex PCR for carbapenemase producers. A total 68 Gram negative uropathogens were isolated and identified by conventional methods. Antibiotic susceptibility test was performed by disk-diffusion technique. Carbapenemase producers were detected phenotypically by modified carbapenem inactivation method among the meropenem resistant isolates. Gene encoding bla NDM and coexistence of bla NDM +bal OXA-48 were identified by multiplex PCR. Results: Twenty (29.41%) meropenem resistant strains were detected among 68 Gram-negative uropathogens. The most common isolates were Escherichia coli and Pseudomonas spp. Among 20 meropenem resistant strains, 19(95%) carbapenemase producers were detected by multiplex PCR, 17(85%) by modified carbapenem inactivation method. The most prevalent gene was blaNDM (94.73%). More than one carbapenemase gene was present in one (5.6%) isolate. Overall, carbapenemase encoding genes were detected in 11.11% of the studied Gram negative uropathogenes. All of the carbapenemase producing organisms were 100% resistant to Ampicillin, Cefuroxime, Ceftriaxone, Ceftazidime, Aztreonam, 94.73% to both Cotrimoxazole and Nitrofurantoin, 68.42% to PipercillinTazobactam and 63.15%, to Amikacin. Conclusion: The study shows that rapid dissemination of blaNDM in Bangladesh demands the effective measures along with antibiotics policies in hospitals which combat the spread of this strains. IAHS Medical Journal Vol 6(1), June 2023; 10-14